(3ZQGFH GdEZJQGH hfRgI GdCdHGH aj GdPgGH hGdGbGeI hGdEjGHs - (3GdGdhSj GdcHjQ , eMehO Hf YHO Gddg GdMSjfj GdGdhSj, TgGH GdOjf CHh GdKfGA,J (B1270 (3g` s ((3HZOGO s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CNP HjOi s
(3BNQgG (B:s
(3HGdNjQ bO CQVJg eSc jahM NJGeg s
(3HChdgG Jedc dGHf GdeUfa fYeGf GdBdhSis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B176 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B175s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B222 s
Keywords: (3GdJGQjNs